OP0254 Cytokine-Induced JNK-Dependent Downregulation of the Forkhead Box O Transcription Factor Foxo1 Promotes Survival and Proliferation of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis. (23rd January 2014) - Grabiec, A. M.; Angiolilli, C.; Hartkamp, L. M.; van Baarsen, L. G.; Tak, P. P.; Baeten, D. L.; Reedquist, K. A.
Abstract : Background: Aberrant regulation of proliferation and survival of immune and stromal cells contributes to the pathogenesis of rheumatoid arthritis (RA). Forkhead box O (FoxO) transcription factors integrate extracellular signals to modulate expression of genes regulating cell cycle and apoptosis, and alterations in activity and expression of FoxO proteins have been reported in several inflammatory diseases, including RA. Objectives: The aim of this study was to examine the relationships between inflammation and FoxO expression in RA, and analyze the mechanisms and biological consequences of cytokine-mediated regulation of FoxO1 expression in RA fibroblast-like synoviocytes (FLS). Methods: RNA was isolated from synovial biopsies obtained by arthroscopy from 20 RA patients and expression of FoxO1, FoxO3a, FoxO4 and IL-6 was measured by quantitative PCR (qPCR). FoxO1 DNA binding, FoxO1 expression and mRNA stability were measured by ELISA-based assays and qPCR in RA FLS stimulated with IL-1β, TNFα, or LPS in the absence or presence of mitogen-activated protein kinase (MAPK) or protein kinase B (PKB) inhibitors. RA FLS were transduced with adenovirus encoding control GFP or a constitutively active FoxO1 mutant (FoxO1ADA) to examine the effects on cell survival and gene expression. FLS viability was analyzed by MTT and ELISA-based apoptosis detection assay. Changes in expression of genes regulated by FoxO1 were analyzed by low density qPCR arrays and confirmed by immunoblotting. Results: In RA synovial tissue expression of FoxO1 negatively correlated with clinical parameters of disease activity: serum C-reactive protein ( R = -0.771, P = 0.0008), erythrocyte sedimentation rate ( R = -0.739, P = 0.0003), and DAS28 ( R = -0.575, P = 0.01), as well as synovial IL-6 mRNA levels ( R = -0.628, P = 0.004). In vitro, RA FLS stimulation with IL-1β or TNFα caused rapid reduction of mRNA levels of FoxO1, but not other FoxO family members. Downregulation of FoxO1 transcript was followed by reduction of FoxO1 protein expression and DNA binding ( P < 0.01). This effect was independent of PKB signaling, which is the main negative regulator of FoxO activity. Instead, FoxO1 downregulation by IL-1β was associated with acceleration of FoxO1 mRNA degradation. Inhibition of c-Jun N-terminal kinase (JNK), but not other MAPKs, prevented reduction of FoxO1 expression and binding by IL-1β, and blocked IL-1β-induced reduction of FoxO1 mRNA stability. Overexpression of constitutively active FoxO1 in RA FLS induced apoptosis associated with altered expression of genes regulating cell viability and cell cycle progression: proapoptotic BIM and the cell cycle inhibitor p27Kip1 were induced while expression of the antiapoptotic Bcl-2-like protein Bcl-XL was suppressed in cells expressing active FoxO1. Conclusions: Collectively, our findings suggest that suppressed synovial FoxO1 expression is strongly associated with RA pathology and demonstrate that reduction of FoxO1 expression might contribute to perpetuation of inflammation and joint destruction in RA by promoting FLS survival and proliferation. Our data also identify JNK-mediated modulation of FoxO1 mRNA stability as an important mechanism underlying regulation of FoxO1 by inflammatory cytokines. Disclosure of Interest: None Declared